Transforming Teacher Performance: The Impact of Training and Professional Development on Competence Improvement - Subekti, Mukodas Arif; Suryadi, Suryadi; Ahmad, Masduki (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3142, 2024)
In order to improve the quality of education, the transformation of teacher performance is crucial and depends on adequate training and continuous professional development that improves competence in various aspects. Structured training programmes that meet the specific needs of teachers are key to creating significant changes in their performance so that they can effectively respond to the challenges of modern education. The purpose of this study is to explore the various elements of the impact of training and professional development including digital competencies that focus on improving teacher performance. This research uses the literature study method as the main approach. The results of this study highlight the importance of ongoing training and professional development to improve teachers' competencies, especially in the face of new challenges such as technology integration. By identifying successful training programmes in various studies, education systems can become more effective in improving teacher performance.. The conclusions of this study confirm that continuous training and professional development, as well as the relevance of training programmes to the teaching context, are key factors in transforming teacher performance. The implementation of a comprehensive training strategy, covering aspects of technology, intercultural skills and evidence-based practice, can significantly improve teachers' competencies and, in turn, student learning outcomes.